EDUCATIONAL INNOVATION IN DEVELOPING QUALITY MANAGEMENT MUHAMMADIYAH BEST ELEMENTARY SCHOOL BANDUNG - Iim Ibrohim; Agus Salim Mansyur; Muhibbin Syah; Uus Ruswandi (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2021)
This research aims to identify the supporting and inhibiting factors of educational innovation implemented by SD Muhamadiyah 7 Kota Bandung. By identifying supporting and inhibiting factors, the implementation of the innovation program is hoped can be more successful. The research method that was used in this research was descriptive qualitative. Data collection techniques through observation, interviews, and documentation study. Data analysis was performed by reducing data, displaying it, taking conclusions, verifying, analyzing, summarizing, and analyzing data. The research results show; supporting and inhibiting factors for educational innovation SD Muhammadiyah 7 Bandung City in developing the quality of school management, some are internal and external.